A comunicação de empresas verdes e a relação com o consumidor consciente - Lorencinho, Mariana Reginato Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This academic work has as its objective to demonstrate the fundamental role of communication as a tool towards implantating an environmental management project in organizations, aswell as familiarizing with the complex relashionship be-tween green businesses and its publics. The concern involving environmental prob-lems are increasing and it directly affects the consumer’s choice and their requests on organizations’ behavior. The integration with all sectors of economy is necessary as a part of a developing process that has as its main objective the environmental conservation and therefore the quality of human life on planet. There is also the question of how in the process of communication there is not an only way of interven-tion, but a continuous reciprocal action. The work is accomplished with an analyses of the green management communication of the business Grupo Abril

O trabalho tem como objetivo demonstrar o papel fundamental da comunica-ção como ferramenta de implantação de um projeto de gestão ambiental nas organi-zações, conhecer a complexa relação entre as empresas verdes e seus públicos. A preocupação com os problemas ambientais é crescente e atinge diretamente a esco-lha do consumidor e suas cobranças em relação ao comportamento das organiza-ções. É necessária a integração de todos os setores da economia como parte de um processo de desenvolvimento que tem por objetivo a preservação do meio ambiente e assim a qualidade de vida humana do planeta. Discute-se também que no proces-so de comunicação não há um caminho único de interferência. Mas sim um proces-so contínuo e de reciprocidade. O estudo se concretiza com a análise da gestão da comunicação verde do Grupo Abril
Keywords: Comunicação; Gestão ambiental; Empresas - Aspectos ambientais; Consumidores; Communication; Environmental management; Consumers